DNA-binding of the Tet-transactivator curtails antigen-induced lymphocyte activation in mice. Issue 1 (December 2017) - Ottina, Eleonora; Peperzak, Victor; Schoeler, Katia; Carrington, Emma; Sgonc, Roswitha; Pellegrini, Marc; Preston, Simon; Herold, Marco; Strasser, Andreas; Villunger, Andreas
Abstract The Tet-On/Off system for conditional transgene expression constitutes state-of-the-art technology to study gene function by facilitating inducible expression in a timed and reversible manner. Several studies documented the suitability and versatility of this system to trace lymphocyte fate and to conditionally express oncogenes or silence tumour suppressor genes in vivo. Here, we show that expression of the tetracycline/doxycycline-controlled Tet-transactivator, while tolerated well during development and in immunologically unchallenged animals, impairs the expansion of antigen-stimulated T and B cells and thereby curtails adaptive immune responses in vivo. Transactivator-mediated cytotoxicity depends on DNA binding, but can be overcome by BCL2 overexpression, suggesting that apoptosis induction upon lymphocyte activation limits cellular and humoral immune responses. Our findings suggest a possible system-intrinsic biological bias of the Tet-On/Off system in vivo that will favour the outgrowth of apoptosis resistant clones, thus possibly confounding data published using such systems. Tet-transactivators are used for direct regulation of gene expression, RNA interference and for CRISPR/Cas9-based systems. Here the authors show that DNA-bound Tet-transactivators can induce cell death in antigen-activated lymphocytes in vivo, putting into question the use of, and in vivo data generated with, these molecular tools.